Strategies for Facing Quarter Life Crisis: The Combination of Religiosity and Peer Pressure in Fresh Graduates - Afdhalia, Afdhalia; Riyanti, Santika; Fitriani, Annisa; Ulpa, Eska Prawisudawati (ANFUSINA: Journal of Psychology, 2024)
The quarter-life crisis is a feeling of anxiety that arises from the uncertainty of life ahead, particularly in relation to relationships, career, and social life, typically occurring in one's 20s. The challenges faced during a quarter-life crisis include issues related to dreams and expectations, academic interests, religion and spirituality, as well as work and career life. These problems emerge when individuals reach the age of 18-29, or after completing their secondary education, such as university students. The academic leap from university to the workforce often causes emotional wounds and instability, leading to an emotional crisis. This study is quantitative and focuses on fresh graduates who graduated during periods 3, 4, and 5 of 2023 at UIN Raden Intan Lampung, who are not yet employed. It uses random sampling to select 249 fresh graduates as respondents. The measurement tools used include scales for quarter-life crisis, religiosity, and peer pressure. Multiple regression analysis was applied to analyze the data, using SPSS 26 for Windows. The analysis revealed a significant relationship between religiosity and peer pressure with the quarter-life crisis, with an R value of 0.348 and an F value of 6.390. The effective contribution was found to be 12.1%. The study also discovered a positive relationship between religiosity and quarter-life crisis in fresh graduates, contributing 10.58%. Furthermore, the study found a negative relationship between peer pressure and quarter-life crisis in fresh graduates, with an effective contribution of 1.50%. Keywords: religiosity, peer pressure, quarter life crisis